The MaNGA firefly value added catalogue: resolved stellar populations of 10 010 nearby galaxies. Issue 4 (6th May 2022) - Neumann, Justus; Thomas, Daniel; Maraston, Claudia; Hill, Lewis; Nanni, Lorenza; Wenman, Oliver; Lian, Jianhui; Comparat, Johan; Gonzalez-Perez, Violeta; Westfall, Kyle B; Yan, Renbin; Chen, Yanping; et al.
ABSTRACT: We present the Mapping Nearby Galaxies at Apache Point Observatory survey (MaNGA) firefly Value Added Catalogue (VAC) – a catalogue of ∼3.7 million spatially resolved stellar population properties across 10 010 nearby galaxies from the final data release of the MaNGA survey. The full spectral fitting code firefly is employed to derive parameters such as stellar ages, metallicities, stellar and remnant masses, star formation histories, star formation rates, and dust attenuation. In addition to Voronoi-binned measurements, our VAC also provides global properties, such as central values and radial gradients. Two variants of the VAC are available: presenting the results from fits using the M11-MILES and the novel MaStar stellar population models. MaStar allows to constrain the fit over the whole MaNGA wavelength range, extends the age-metallicity parameter space, and uses empirical spectra from the same instrument as MaNGA. The fits employing MaStar models find, on average, slightly younger ages, higher mass-weighted metallicities, and smaller colour excesses. These differences are reduced when matching the wavelength range and converging template grids. We further report that firefly stellar masses are systematically lower by ∼0.3 dex than masses from the MaNGA PCA and Pipe3D VACs, but match masses from the NSA best with only ∼0.1-dex difference. Finally, we show that firefly stellar ages correlate with spectral index age indicators H δA and D n (4000), though with a clear additional metallicity dependence.